Why do We Owe Our Life to Photosynthesis - Gurevitz, Michael (European Journal of Applied Sciences, 2023)
Curiosity is a key driving force in the development of our cognition, and still the majority of humanity has no idea about basic biological mechanisms that enable life. In large, such ignorance arises firstly from apathy as well as unwillingness to spend the minimal effort on issues unrelated to daily commitments. Secondly, scientific curiosity about basics of our life is negligible in the life of most religious people: everything is in God’s hands, so why care? Still, every single person knows that oxygen (O2) is crucial for life, although the underlying reason and its source remain obscure. Therefore, the objective of this commentary is to explain briefly in a simplified non-elaborative manner how oxygen is being produced in the photosynthetic process by plants, green algae (cyanobacteria=blue-green algae), and bacteria.